2011
DOI: 10.1016/j.ymgme.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Optimized loading test to evaluate responsiveness to tetrahydrobiopterin (BH4) in Brazilian patients with phenylalanine hydroxylase deficiency

Abstract: INTRODUCTION:Recent studies showed that phenylalanine (Phe) plasma concentrations may decrease in some patients with hyperphenylalaninemia (HPA) due to phenylalanine hydroxylase (PAH) deficiency, after the administration of tetrahydrobiopterin (BH(4)). OBJECTIVE: To determine responsiveness to a single dose of BH(4) administered according to an innovative protocol using a combined Phe and BH(4) loading test in Brazilian phenylketonuria (PKU) patients. METHODS: Patient age should be 4 years, and median Phe plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[30][31][32] In our study, most of the centers used the 24-hour (52.9%) or 48-hour (32.6%) protocols. The test dose ranged from 5 to 20 mg/kg, with most of the centers (92.3%) using 20 mg/kg.…”
Section: Figurementioning
confidence: 89%
“…[30][31][32] In our study, most of the centers used the 24-hour (52.9%) or 48-hour (32.6%) protocols. The test dose ranged from 5 to 20 mg/kg, with most of the centers (92.3%) using 20 mg/kg.…”
Section: Figurementioning
confidence: 89%
“…An optimized 48-hour BH 4 loading test, with two BH 4 administrations (20 mg/kg bw/day) on two consecutive days has been proposed more recently [24]. Other modified BH 4 loading test schemes have also been proposed [12,14,21,22,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Of the four genotypes involving p.V388M described by Sarkissian et al (2012) , was also reported as responsive in sapropterin clinical trials, according to Sarkissian et al (2012). Among Ibero-American patients tested by BH 4 loading tests, p.V388M appeared to be at least ambiguously responsive-of the three Spanish patients homozygous for this mutation reported by Aldamiz-Echevarria et al (2016), one was BH 4 responsive, and in Brazil, Nalin et al (2011) reported one homozygous patient for p.V388M, and he was BH 4 responsive.…”
Section: Discussionmentioning
confidence: 92%
“…(), one was BH 4 responsive, and in Brazil, Nalin et al. () reported one homozygous patient for p.V388M, and he was BH 4 responsive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation